Proteomic analysis reveals a proteolytic feedback loop in murine seminal fluid. Issue 13 (14th June 2013) - McKee, Chad M.; Xu, Danmei; Kessler, Benedikt M.; Muschel, Ruth J.
Abstract BACKGROUND Matrix metalloproteinase 9 (MMP9) has been implicated in extracellular matrix (ECM) remodelling, angiogenesis and inflammation. However, the targets for proteolysis that lead to these physiological consequences are often undefined as is the regulation of MMP9 itself. Therefore, identification of both the potential direct and indirect targets of MMP9 is critical for further understanding the effects of its proteolytic cascades. METHODS To study these cascades on a wider scale, transgenic mouse "knock‐out" models and ultra‐high performance liquid chromatography mass spectroscopy (UPLC‐MSE) were used to elucidate the MMP9 targets, inhibitors, and interactors found in mouse seminal vesicle fluid (SVF). RESULTS Proteomics analysis of SVF from wild type, mmp9−/− or pn1−/− mice detected differences in serine protease inhibitors (serpins), reproductive proteins, developmental regulators, and cancer proto‐oncogenes, including Renin 1/2. Protease nexin 1 (PN1), an ECM‐based inhibitor of urokinase, was elevated in the SVF of mmp9−/− mice. We observed that MMP9‐mediated N‐terminal cleavage of PN1 reduces this serpin's functional activity. Our data also suggest a feedback loop in which inhibition of PN1 is a critical step in permitting greater activity of MMP9. CONCLUSION This study extends the degradome of MMP9 and examines components relevant to seminal fluid physiology. PN1 is proposed to be a novel inhibitor of MMP9 activity and a block to collagen cleavage, a frequent antecedent to cancer cell invasion. The interaction of MMP9 with PN1 and other serpins may lead to a better understanding of seminal vesicle function and possible impacts on fertility, as well as provide novel therapeutic targets. Prostate 73: 1427–1440, 2013. © 2013 Wiley Periodicals, Inc.